Aplicación móvil para el aprendizaje de matemáticas del 5to. año de EGB de la Escuela Augusta Mora de Franco - Cujilema Muyulema, Janneth Maribel; Armijos Mora, Steven Ariel (Machala, 2022)
This research project was carried out in the School of Basic Education "Augusta Mora de Franco" in the city of Machala, with the participation of Maria Esther Peña Bravo and the participation of 35 students who make up the fifth year of EGB. During the Ccovid-19 pandemic, the Ministry of Education opted for teachers to provide online classes and that students can receive classes from the comfort of their homes so as not to risk this disease. It should be noted that ICTs are currently being incorporated into the educational context, bringing with it innovative changes, new tools and technological resources that allow students to stengthen their learning. Mobile Applications are educational technological tools that in the online modality are being incorporated in the development of the class with the objective that the student stengthens the learning process through the resolution of mathematical exercises. By implementing mobile Applications in the development of the class, we intend that students interact and participate, with the aim of strengthening meaningful learning, since the use of mobile Apps is an innovate tool. Therefore, as a group of researchers, we pose the question: How to strengthen the learning of basic operations in ths subject of mathematics in the students of the 5th year of EGB of the School of Basic Education "Augusta Mora de Franco" in the city of MACHALA? That is why we decided to develop a mobile Application that contains of the basic operations of the sbject mathematics in order to achieve motivation, interaction and high participation by students, which is why the general objectiveof this project is to create a mobile Application called "Maths" through App Inventor to strengthen the kearning of divisions in the Fifth Year of EGB in the School of Basic Education "Augusta Mora de Franco". In order to demonstrate the degree of satisfaction with the mobile Application, the qualitative Approach was based on an interview with the teacher in online mode consisting of 9 open questions and a quantitative survey was Applied to tha students which was composed of 6 closed questions of yes and no since they are students from 8 to 9 years of age, where through the answers they indicated that the mobile Application is an interactive and intuitive technological tool for its colors, images, exercises and a game. With the results obtained it was possible to conclude that the teacher of the institution will incorporate the Maths mobile Application in the subject of mathematics because it was evidenced that most of the students participate in the resolution of the exercises (addition, subtraction, multiplication, subtraction, division), in addition to interacting with the teacher. The contents and exercises that were incorporated in the Maths mobile Application are in accordance with the PUD (Teaching Unit Plan) given by the teacher of the institution.
El presente proyecto de investigación se llevó a cabo en la Escuela de Educación Básica "Augusta Mora de Franco" en la ciudad de Machala, con la participación de la Lcda. María Esther Peña Bravo y participación de los 35 estudiantes que conforman el Quinto año de EGB. Durante la pandemia del Covid-19 el ministerio de educación optó a que los docentes brinden clases online y que los estudiantes puedan recibir clases desde la comodidad de su casa para no arriesgarse ante esta enfermedad. Cabe recalcar que en la actualidad las TIC se están incorporando en contexto educativo que trae consigo cambios innovadores, nuevas herramientas y recursos tecnológicos que le permiten a los estudiantes fortalecer el aprendizaje. Las aplicaciones móviles son herramientas tecnológicas educativas que en la modalidad online se están incorporando en el desarrollo de la clase con el objetivo de que el estudiante fortalezca el proceso de aprendizaje a través de la resolución de los ejercicios matemáticos. Nosotros al implementar aplicaciones móviles en el desarrollo de la clase pretendemos que los estudiantes interactúen y participen, con el objetivo de fortalecer el aprendizaje significativo ya que el uso de las Apps móviles son una herramienta innovadora. Por ello nosotros como grupo de investigadores, planteamos como interrogante ¿Cómo fortalecer el aprendizaje de las operaciones básicas en la asignatura de matemáticas en los estudiantes del 5to año de EGB de la Escuela de Educación Básica "Augusta Mora de Franco" de la ciudad de MACHALA? Es por ello que decidimos elaborar una aplicación móvil que contenga ejercicios de las operaciones básica de la asignatura matemáticas con la finalidad de conseguir motivación, interacción y una alta participación por parte de los estudiantes, es por ello que se plantea como objetivo general del presente proyecto crear una aplicación móvil denominada "Maths" mediante App Inventor para fortalecer el aprendizaje de las divisiones en el Quinto Año de EGB en la Escuela de Educación Básica "Augusta Mora de Franco". Para evidenciar el grado de satisfacción que tuvo la aplicación móvil se basó en los enfoques cualitativo en donde se realizó una entrevista a la docente en modalidad online que constaba de 9 preguntas abiertas y en tanto a lo cuantitativo se aplicó una encuesta a los estudiantes la cual estaba compuesta por 6 preguntas cerradas de si y no ya que son estudiantes de 8 a 9 años de edad, donde a través de las respuestas nos indicaron que la aplicación móvil es una herramienta tecnológica interactiva e intuitiva por sus colores, imágenes, ejercicios y un juego. Con los resultados obtenidos se pudo concluir que la docente de la institución si va incorporar la aplicación móvil Maths en la asignatura de mateemáticas porque se evidenció que la mayoría de los estudiantes participan para la resolución de los ejercicios (suma, resta, multiplicación, resta, división), además que interactúan junto con la docente. Los contenidosy ejercicios que se incorporaron en la aplicación móvil Maths están de acuerdo al PUD (Plan de Unidad Didáctica) otorgado por la docente de la institución.
Keywords: APLICACION MOVIL; INTERACCION; APRENDIZAJE SIGNIFICATIVO; MOTIVACION